2015
DOI: 10.1016/j.jpsychores.2014.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Adverse life events and health: A population study in Hong Kong

Abstract: Considering the high prevalence of traumatic events and how common the conditions associated with such events are in the general population, screening for adverse life events as part of comprehensive assessment will allow a deeper understanding of patients' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…Furthermore, we need to mention the shortcoming of catching data by an administrative database. A population study ( Karatzias, Yan & Jowett, 2015 ) showed a significant relationship between the death of a partner and heart disease, but a specific association with AF needs further research. In detail, results reported in these studies might reflect biased effects, particularly as related to assessment procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we need to mention the shortcoming of catching data by an administrative database. A population study ( Karatzias, Yan & Jowett, 2015 ) showed a significant relationship between the death of a partner and heart disease, but a specific association with AF needs further research. In detail, results reported in these studies might reflect biased effects, particularly as related to assessment procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, MCS dimension includes the social functioning, emotional problems, mental health and vitality domains [ 24 ]. The scores are standardized to population norms (based on a European normative sample), with the mean score set at 50 (SD = 10); scores above 50 indicate better perception of health status [ 25 ]. The method used to compute values for the two main dimensions (PCS and MCS) was based on the algorithm provided by Andersen et al [ 26 ], which was based on the procedure described in the SF-12 manual.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we need to mention the shortcoming of catching data by an administrative database. A population study [Karatzias, Yan & Jowett, 2015] showed a significant relationship between the death of a partner and heart disease, but a specific association with AF needs further research. In detail, results reported in these studies might reflect biased effects, particularly related to assessment procedures.…”
Section: Discussionmentioning
confidence: 99%